2020
DOI: 10.1002/lsm.23226
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Bubble Oscillations During Laser‐Activated Irrigation of Root Canals and Method of Improvement

Abstract: Background and Objectives: Laser-activated irrigation of dental root canals is being increasingly used as its efficacy has been shown to be superior compared with conventional techniques. The method is based on laser-initiated localized fluid evaporation and subsequent rapid bubble expansions and collapses, inducing microfluid flow throughout the entire volume of the cavity. The irrigation efficacy can be further improved if optimally delayed "SWEEPS" double laser pulses are delivered into the canal. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…It is to be noted that while the X‐SWEEPS modality achieved three times higher removal rate compared with AutoSWEEPS, its performance strongly depends on the chosen time delay of the second pulse. For optimal flushing rate, the X‐SWEEPS delay must approximately match the bubble oscillation time that varies depending on the treated root canal geometry [30]. When during clinical procedures no feedback or other method is available to optimize the pulse delay for particular tooth geometry, the AutoSWEEPS modality represents a more robust and preferable choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be noted that while the X‐SWEEPS modality achieved three times higher removal rate compared with AutoSWEEPS, its performance strongly depends on the chosen time delay of the second pulse. For optimal flushing rate, the X‐SWEEPS delay must approximately match the bubble oscillation time that varies depending on the treated root canal geometry [30]. When during clinical procedures no feedback or other method is available to optimize the pulse delay for particular tooth geometry, the AutoSWEEPS modality represents a more robust and preferable choice.…”
Section: Discussionmentioning
confidence: 99%
“…When using X-SWEEPS modality in clinical practice, it is important to consider that the bubble oscillation time (T B ) depends, among other parameters, on the diameter of the cavity [25,30], and that the dimensions of the access cavity vary from tooth to tooth. Therefore, the X-SWEEPS modality requires the practitioner to adjust the X-SWEEPS pulse separation T p to the dimension of the access cavity in order to obtain consistent enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Recently [38], it was shown that for long liquid‐filled cylindrical cavities (i.e., tubes) with diameter D cavity , the bubble oscillation time T B can be well described by a function: T normalB = T B . i n f ( 1 + K / D c a v i t y ) where K is the fitting parameter and T B.inf is the bubble oscillation time in an infinite reservoir ( D cavity ≈ ∞) for a particular set of laser and FT parameters. The ratio T B / T B.inf was found to be independent of the laser pulse energy E L , with the best fit obtained for K = 3.52 mm where the statistical coefficient of determination R 2 = 0.96…”
Section: Methodsmentioning
confidence: 99%
“…When the temporal separation ( T p ) between the two SWEEPS laser pulses is fixed using the “X‐SWEEPS” modality, the largest enhancement of shock waves and internal irrigant pressures occurs when T p does not deviate substantially from the optimal separation time ( T opt ), corresponding to the time when the second laser pulse of the X‐SWEEPS pulse pair is delivered near the end of the collapse phase of the primary bubble generated by the first laser pulse ( T opt ≈ T B ) [ 24 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation